The Making Menir as Fortified Rice Milk: A Healthy and Economical Innovation of the Housewife’s Pioneering Business: Menir Jadi Susu Beras Fortifikasi: Inovasi Sehat dan Ekonomis Dalam Upaya Rintisan Usaha Ibu Rumah Tangga - Elisabeth Nainggolan; Petrus Loo; Susan Grace Nainggolan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
This community service activity was organized by the PKM team from the Eka Prasetya College of Economics. The activity took the form of a training workshop on making groats into fortified milk for the PKK (Family Welfare Movement) women's group in Pematang Johar Village. This community service activity was carried out to increase knowledge about creative economic innovations and improve innovative skills in creating creative economic products by utilizing the potential of local resources. Groats into fortified milk has the potential to be an alternative food with added value and economic potential because it can be developed into a business. The results of this community service activity are ready-to-sell fortified groats milk products. This product opens up business opportunities that can have an impact on increasing household income.